Frontiers in Chemistry: Rising Stars - Suib, Steve; Ju, Huangxian; Cosnier, Serge; Ohtani, Bunsho; Wade, John D.; Garnier, Gil; Vincent Myung, Nosang; Carlos, Luís D.; Kassiou, Michael; Zhang, Fan; Ojima, Iwao; Musto, Pellegrino; et al. (Frontiers Media SA, 2020)
The Frontiers in Chemistry Editorial Office team are delighted to present the inaugural "Frontiers in Chemistry: Rising Stars" article collection, showcasing the high-quality work of internationally recognized researchers in the early stages of their independent careers. All Rising Star researchers featured within this collection were individually nominated by the Journal's Chief Editors in recognition of their potential to influence the future directions in their respective fields. The work presented here highlights the diversity of research performed across the entire breadth of the chemical sciences, and presents advances in theory, experiment and methodology with applications to compelling problems. This Editorial features the corresponding author(s) of each paper published within this important collection, ordered by section alphabetically, highlighting them as the great researchers of the future. The Frontiers in Chemistry Editorial Office team would like to thank each researcher who contributed their work to this collection. We would also like to personally thank our Chief Editors for their exemplary leadership of this article collection; their strong support and passion for this important, community-driven collection has ensured its success and global impact.